Pre-natale sterfte en ritueel: Die behoefte aan "n betekenisvolle ritueel in die hantering van "n miskraam of aborsie - Nel, Johan (HTS teologiese studies, 2007)
Pre-natal death: The need for employing a meaningful ritual towards coping with a miscarriage or an abortion Both religion and ritual amongst others are ways by which people can express feelings in their relationships with others, the world and the Almighty God. Religion and ritual are often used to come to a better understanding and to cope with loss. In the postmodern era, a holistic approach towards therapies has been developed. Pastoral therapy is a part of this process. This article examines the use of rituals as a possible therapeutical method for coming to terms with loss after the occurence of pre-natal death. The article argues that a meaningful ritual can be used to assist people who have experienced miscarriage or abortion.